2023
DOI: 10.3389/fneur.2023.1221266
|View full text |Cite
|
Sign up to set email alerts
|

Reactive gliosis and neuroinflammation: prime suspects in the pathophysiology of post-acute neuroCOVID-19 syndrome

Jacob Saucier,
Dominique Comeau,
Gilles A. Robichaud
et al.

Abstract: IntroductionAs the repercussions from the COVID-19 pandemic continue to unfold, an ever-expanding body of evidence suggests that infection also elicits pathophysiological manifestations within the central nervous system (CNS), known as neurological symptoms of post-acute sequelae of COVID infection (NeuroPASC). Although the neurological impairments and repercussions associated with NeuroPASC have been well described in the literature, its etiology remains to be fully characterized.ObjectivesThis mini-review ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 98 publications
(186 reference statements)
0
4
0
Order By: Relevance
“…As a microtubule inhibitor used to treat gout, colchicine possesses anti-inflammatory properties that appear beneficial in long-COVID. Specifically, by suppressing microglial activation and attendant release of cytokines, like IL-1β, TNF-α, and nitric oxide, colchicine may interrupt self-amplifying cycles of immunemediated dopaminergic injury centered on the basal ganglia [59,60]. Researchers posit that subsequent reductions in aberrant microglial pruning allow recovery of disrupted motivation/reward and motor control pathways [60].…”
Section: Therapeutic Opportunitiesmentioning
confidence: 99%
“…As a microtubule inhibitor used to treat gout, colchicine possesses anti-inflammatory properties that appear beneficial in long-COVID. Specifically, by suppressing microglial activation and attendant release of cytokines, like IL-1β, TNF-α, and nitric oxide, colchicine may interrupt self-amplifying cycles of immunemediated dopaminergic injury centered on the basal ganglia [59,60]. Researchers posit that subsequent reductions in aberrant microglial pruning allow recovery of disrupted motivation/reward and motor control pathways [60].…”
Section: Therapeutic Opportunitiesmentioning
confidence: 99%
“…Neurological manifestations are major complications of PCC, affecting one-third of patients, with symptoms persisting for more than a month post-COVID-19 infection [33]. According to the above findings, the patients with PCC exhibited a series of symptoms related to reactive gliosis and neuroinflammation in the CNS, including neuropsychiatric manifestations such as fatigue, 'brain fog' (characterized by short-term memory loss and difficulty concentrating), headache, drowsiness, cognitive impairment, sleep disorders, mood changes, disorders of smell or taste, myalgias, anxiety, posttraumatic stress, depression, sleep disturbances, sensorimotor deficits (neuropathy, paresthesia, weakness, and myalgia), and dysautonomia [1,2,[34][35][36][37][38]. Among the PCC symptoms, prolonged cognitive dysfunction is one of the most common impairments affecting between 17 and 28% of the individuals, and in some cases, persisting for several years.…”
Section: Neuroinflammation and Oxidative Stress In The Pccmentioning
confidence: 99%
“…Interestingly, not only a shortage of trophic support but also overnutrition in the postnatal period was postulated to trigger hypothalamus astrogliosis in rat models [121]. Astrogliosis is also a common feature of other neonatal disease conditions like intraventricular hemorrhages in pre-term children [122], neuroinflammation evoked by sepsis [123], hyperbilirubinemia [124], and other intrauterine and postnatal infections (especially in preterm born children), including coronavirus disease 2019 (COVID-19) inflammation [125,126]. In recent studies, SARS-CoV-2 was shown to exhibit tropism towards human cortical astrocytes [127,128].…”
Section: Neonatal Disorders: Reactive Astrogliosis In the Selected Ne...mentioning
confidence: 99%